The combination of biochar and PGPBs stimulates the differentiation in rhizosphere soil microbiome and metabolites to suppress soil‐borne pathogens under consecutive monoculture regimes. Issue 1 (9th November 2021) - Wu, Hongmiao; Wu, Huiming; Jiao, Yanyang; Zhang, Zhongyi; Rensing, Christopher; Lin, Wenxiong
Abstract: The application of biochar and plant‐growth‐promoting bacteria (PGPBs) in biocontrol soil‐borne pathogens has garnered worldwide interest recently. However, how agricultural replanting disease is alleviated by a combination of biochar and PGPBs treatment (SYBB) remains largely unexplored. In this study, we investigated the beneficial effects of single biochar addition and the combination of biochar and PGPBs on alleviating replanting disease by altering the rhizosphere microbiome and metabolites. Our field experiment showed that the SYBB treatment had a better alleviating effect on replanting disease than the single biochar addition. The study indicated the dominant effect of deterministic processes on the bacterial community and of stochastic processes on the fungal community under biochar and PGPBs treatment. The combination of biochar and PGPBs tended to convert the stochastic processes of fungal community assembly into deterministic processes. We found SYBB treatment increased the abundance of potentially beneficial Pseudomonas, Lysobacter, Gemmatimonadetes and Nitrospira, and decreasing the abundance of potentially pathogenic Fusarium, Talaromyces and Fusarium oxysporum . Moreover, the SYBB treatment increased the abundances of carbohydrates, fatty acids and plant hormones, and decreased the abundances of amino acids in the rhizosphere soil. Co‐occurrence network analysis indicated that SYBB treatment increased the connections within the microbial communities and drove the alteration of co‐occurrence network among the microbial communities and metabolites, which increased positive correlations in bacteria‐metabolite networks and decreased positive correlations in fungi‐metabolite networks. Spearman correlation analysis showed the abundances of beneficial Streptomyces, Pseudomonas and Lysobacter were significantly and positively correlated to the metabolites most increased under SYBB treatment. The combination of biochar and PGPBs alleviated replanting disease by mediating the change of rhizosphere soil metabolites, and stimulating the proliferation of indigenous and beneficial soil microbes. The research results are intended to provide the basis for new strategies for green and sustainable remediation of soil‐borne pathogens. Abstract : The combination of biochar and plant‐growth‐promoting bacteria (PGPBs) treatment (SYBB) had a better alleviating effect on replanting disease than the single biochar addition. The study indicated the dominant effect of deterministic processes on the bacterial community and of stochastic processes on the fungal community under biochar and PGPBs treatment. The SYBB treatment was able to extend bacterial niche breadth and decrease fungal niche breadth. The combination of biochar and PGPBs stimulated the indigenous and beneficial soil microbes to suppress host‐specific pathogens by mediating an increase production of rhizosphere soil metabolites, further alleviating the serious replanting disease.